Handbook for Legal Exam Preparations Including Writing Principles at LL.B., Barrister-at-Law, Assistant Public Prosecutor and Judge Trainee Levels, Together with the Guidance to Study LL.M. Abroad - Satpradit, Pinyok (Mae Fah Luang University Law Journal, 2020)
Handbook for Legal Exam Preparations including Writing Principles at LL.B., Barrister-at-Law, Assistant Public Prosecutor and Judge Trainee Levels, together with the Guidance to Study LL.M. Abroad written by Ponpawit Pankhamkerd is the handbook which compiles the author’s experiences and the interesting information. This book aims to pass on knowledge as a guideline for studying and preparing legal exam in Thailand. Furthermore, Waranya Trongpisutsak is also a co-author of this handbook, who provides guidance related to study LL.M. Abroad. The handbook is suitable for people who desire to study or who are studying at LL.B. and prepare to take legal exams, namely Barrister-at-Law, Assistant Public Prosecutor and Judge Trainee Levels, as well as people who desire to preparing to study LL.M. Abroad.